Determinants of loyalty in GCC Islamic banks: an exploratory study - Alobaad, Alaa; Abduh, Muhamad; Abdin, Thawab (2014)
Nowadays, protecting market share against rival firms is more important than ever due to the decline in market growth rate and the increase in the competition. The main requirement for protecting market share is to create loyal customers. Management needs to realize the effects of customer loyalty on business growth and profits. Therefore the main objective of this paper is to examine customer satisfaction and loyalty upon Islamic banks particularly in GCC countries and find interrelationships between service quality, emotional satisfaction, and image on attitudinal and behavioral loyalty. By using survey‚ data of this study were collected from a convenience sample of 600 Islamic banking customers. The outcomes of this study might have useful implications as a guideline for economic decision-makers, banks, and GCC governments since it can reduce switching phenomenon in banks which also increases the profitability.